The Relationship Between Quantitative C-Reactive Protein (CRP) and the Number of Leukocytes and Blood Edition Rate (ESR) in Optic Neuritis Patients - Ramadhayanti, Lidya; Hafy, Zen; Sari, Nurmalia Purnama (GLOBAL HEALTH SCIENCE GROUP, 2024)
Optic neuritis (ON) is a demyelinating inflammatory process that causes sudden visual impairment that can occur in one or both eyes simultaneously or successively. Optic neuritis (ON) can be caused by demyelinating diseases of the central nervous system, immune system diseases, infectious diseases, and can also be caused by inflammatory responses and vaccinations. This study aimed to determine the relationship between quantitative c-reactive protein (CRP) and leukocyte count and blood edition rate (ESR) in patients with optic neuritis. The most common pathophysiology of optic neuritis is inflammatory optic neuropathy associated with multiple sclerosis. In optic neuritis, demyelination occurs due to inflammation of the optic nerve with a lesion pathology similar to plaque in the central nervous system of someone with multiple sclerosis. There will be perivascular swelling, edema of the myelinated nerve sheath, and myelin damage. Inflammation of the retinal vascular endothelium may precede demyelination. Myelin damage is more severe than the damage found in axons. This research was conducted to determine the correlation between quantitative CRP levels and leukocyte counts and erythrocyte sedimentation rate levels in optical neuritis patients. The type of research used is quantitative research with an analytical observational research design, namely a cross-sectional approach. CRP and ESR are two commonly performed laboratory tests that may help physicians in accurately diagnosing and following many complex disease conditions. The relationship between CRP levels and leukocyte counts is to evaluate the effectiveness of treatment response.